Prediction of Land Cover Change in Wae Heru Watershed Ambon City Using Celular Automata Markov Chain - Manakane, Susan E; Latue, Philia Christi; Somae, Glendy; Rakuasa, Heinrich (Journal of Geographical Sciences and Education, 2023)
Land cover change in the watershed area in Ambon City has an impact on land degradation, water pollution, flooding and erosion. Therefore, the utilization and efficiency of land cover in the watershed area must be improved based on sustainable land cover planning.  This study aims to analyze land cover changes in the Wae Heru watershed, Ambon City in 2013, 2018, and 2023 and predict land cover in 2028.  This study used the CA-Markov method to predict land cover in 2028. The results showed that in 2013 the built-up land had an area of 74.25 ha, in 2018 an area of 79.30 ha and in 2023 an area of 88.00 ha and the results of the 2028 prediction of built-up land were 116.96 ha, this is certainly influenced by the increasing number of residents who continue to grow every year. Agricultural land, non-agricultural land and open land continue to decrease in area. The results of this prediction are very useful for the government in making policies related to sustainable spatial planning in the future.